2020
DOI: 10.1097/inf.0000000000002495
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Catheter Management in High-risk Children With Bloodstream Infections

Abstract: Background: National guidelines recommend removal of central venous catheters (CVCs) for central line–associated bloodstream infections (CLABSIs) caused by Staphylococcus aureus, Pseudomonas aeruginosa, and fungi. Data regarding guideline compliance and rates of associated treatment failures in pediatric patients with attempted CVC salvage are limited. Methods: We performed a retrospective analysis of high-risk children (age ≤ 21 years) hospitalized fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…The cumulative incidence estimated in this study is higher than the 1 expected by clinicians based on the scarce previously published literature. 12–20 Differences with previous literature can be explained by multiple reasons. First, successful salvage was defined taking into account the clinical status of the patient and not solely CVC removal or reinfections as done by previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…The cumulative incidence estimated in this study is higher than the 1 expected by clinicians based on the scarce previously published literature. 12–20 Differences with previous literature can be explained by multiple reasons. First, successful salvage was defined taking into account the clinical status of the patient and not solely CVC removal or reinfections as done by previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…However, in cases when the catheter is not the source of sepsis, it deserves a prospective, randomized controlled trial to document whether prompt catheter removal contributes significantly to the outcomes as it is often difficult to reinsert the CVC during the critically ill period. Because of different study designs, cohort selections, and perhaps the bias of illness severity, previous studies failed to have undebatable conclusions [ 31 , 32 , 33 , 36 ]. Nevertheless, we suggest that CVC removal at earliest stage of sepsis should be considered for neonates with candidemia, based on our study result and the current guidelines [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hecht et al reported real-world data showing that the compliance rate was poor, and attempted CVCs salvage resulted in a high treatment failure rate for high-risk children with bloodstream infections (BSI), although the guideline recommends CVC removal for CLABSI [5]. This is understandable, as clinicians must decide between risking CVCs infection and CVC salvage or allowing CV retention, as CVC removal can result in remnant CV loss and directly lead to a poor prognosis in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%